Translational Immunogene Therapy in Veterinary Oncology: Recent Clinical Trial Evidence in Companion Animal Cancers - Haryo, Albiruni (Media Kedokteran Hewan, 2026)
Cancer in dogs and cats is a major cause of illness and death and provides clinically relevant models for comparative oncology. Purpose: This review critically evaluates clinical trials of gene immunotherapy in client-owned dogs and cats from 2017 to 2024, with an emphasis on methodological quality, antitumor efficacy, safety, and translational relevance to human oncology. Review(s): Systematic searches identified trials in spontaneous cancers treated with gene-based immunotherapies or genetically modified cells that reported at least one clinical and one safety outcome. The evidence base is limited but coherent and dominated by non-viral plasmid vectors delivered by gene electrotransfer for melanoma, mast cell tumors, mammary adenocarcinoma, osteosarcoma, and sarcoid. Expression of cytokines, such as interleukin-12, and tumor-associated antigens was generally well tolerated, with mostly local, mild, and transient adverse effects and minimal systemic toxicity. Reported benefits included improved local tumor control, delayed recurrence or metastasis, enhanced quality of life, and prolonged survival in selected studies. Conclusion: Larger, multi centre, biomarker-rich, and controlled trials are needed to clarify immune mechanisms, strengthen causal inference, and optimize cross-species clinical protocol design.